The correlation between continuing professional development and creative pedagogical activities - Sukma Dwiaugita; Sri Kusuma Ningsih (English Teaching Journal : A Journal of English Literature, Language and Education, 2023)
Continuing Professional Development (CPD) contributes to developing teacher professionalism in creating creative pedagogical activities that attract students' learning interests. Teachers' active participation in CPD could update how they teach to meet the needs of their students in increasing students’ learning outcomes. The study aimed to determine the correlation between CPD and creative pedagogical activities. There were 100 Indonesian English teachers involved in the study. Data were obtained from close-ended questionnaires focused on CPD and teachers’ creativity and then analyzed using correlational statistics. This study showed a positive correlation between the two variables that provide teachers with a framework for comprehending creativity and its significance to their professional development.